The Legal and Regulatory Response to Solicitors Involved in Serious Fraud: Is Regulatory Action More Effective than Criminal Prosecution? - Middleton, David J. (The British journal of criminology, 2005)
The legal and regulatory responses to serious fraud can result in multiple proceedings against the alleged perpetrators. Drawing on a comparison of the regulatory and criminal-justice action taken against solicitors drawn into high-yield investment frauds, empirical evidence of an apparently more effective regulatory response is presented and the problems of multiple or parallel proceedings (including in the civil courts) are considered in the light of recent case law. The differing objectives of regulatory, criminal-justice and civil proceedings are discussed. Ultimately, this article addresses the appropriate legal and regulatory response to dishonesty or serious misconduct by solicitors - an issue which has received little attention in recent years